Multi-level and Multi-Actor Governance of National Health Insurance Scheme in Ghana: An exploration of the perceived challenges in the Bosumtwi District - OWUSU, Nicodemus Osei; MENSAH, Agnes Tweneboah; OPPONG, nana Yaw (Journal of Governance and Public Policy, 2019)
National health insurance scheme has been used as a strategy to address health inequalities in Ghana in the past ten years. In ensuring all inclusive governance, the government has instituted a system which aims at bringing together various actors at all levels of government. However, little is known about the challenges involved in such multi-level and multi-actor system. In order to open this ‘black box’, we explored the views of those involved at the district levels to understand the challenges that are associated with this system of governance. We used face-to-face interviews and document review. The study area was Bosumtwi District and the sample size was 25 stakeholders. Data were recorded and later analysed. The findings of the study revealed some challenges which include: working with different set of stakeholders with incompatible interests and divergent goals; the existence of power differentials; limited opportunities for various stakeholders at lower levels to make independent decisions and finally, the problem of coordinated action. It was concluded that while the system is a laudable idea, it would be better if such system helps to bring various actors to existing hierarchical and state-centric apparatuses so as to enhance better coordination of ideas.